Landfill leachate treatment by coagulation/flocculation combined with microelectrolysis-Fenton processes. Issue 14 (20th June 2019) - Luo, Kun; Pang, Ya; Li, Xue; Chen, Fei; Liao, Xingsheng; Lei, Min; Song, Yong
ABSTRACT: Landfill leachate was pretreated by chemical flocculation with polyaluminum chloride (PAC) as a flocculant, and subsequently purified by the microelectrolysis-Fenton (MEF) process. Response surface methodology was employed to optimize the MEF process, and the optimal conditions were initial pH 3.20, H2 O2 concentration 3.57 g/L, and Fe-C dosage 104.52 g/L. The PAC coagulation combined with MEF processes obtained a superior decontamination performance, and the predicted chemical oxygen demand (COD) and humic acids (HA) removal were respectively 90.27% and 93.79%. The strong fluorescence peak at 425 nm and the trapping experiment showed that ⋅ OH was generated during MEF, which had a strong oxidation ability to degrade organic recalcitrant pollutants. The ultraviolet–visible spectra and three-dimensional excitation–emission matrices spectra (3D-EEMs) indicated that PAC coagulation could preferentially remove protein-like substances, while the MEF process was effective in destructing organic recalcitrant pollutants, especially humic-like and fulvic-like substances.